Experimental study on the role of the target electron temperature as a key parameter linking recycling to plasma performance in JET-ILW*This manuscript has been authored by UT-Battelle, LLC, under contract DE-AC05-00OR22725 with the US Department of Energy (DOE). The US government retains and the publisher, by accepting the article for publication, acknowledges that the US government retains a nonexclusive, paid-up, irrevocable, worldwide license to publish or reproduce the published form of this manuscript, or allow others to do so, for US government purposes. DOE will provide public access to these results of federally sponsored research in accordance with the DOE Public Access Plan (http://energy.gov/downloads/doe-public-access-plan). (1st June 2022) - Lomanowski, B.; Dunne, M.; Vianello, N.; Aleiferis, S.; Brix, M.; Canik, J.; Carvalho, I.S.; Frassinetti, L.; Frigione, D.; Garzotti, L.; Groth, M.; Meigs, A.; et al.
Abstract: Changes in global and edge plasma parameters ( H 98(y, 2), dimensionless collisionality ν *, core density peaking, separatrix density n e, sep ) with variations in the D2 fueling rate and divertor configuration are unified into a single trend when mapped to ⟨ T e, ot ⟩, the spatially averaged spectroscopically derived outer target electron temperature. Dedicated JET with the ITER-like wall (JET-ILW) experiments in combination with an extended JET-ILW database of unseeded low-triangularity H-mode plasmas spanning a wide range of D2 fueling rates, I p, B t and heating power have demonstrated the importance of ⟨ T e, ot ⟩ as a key physics parameter linking the recycling particle source and detachment with plasma performance. The remarkably robust H 98(y, 2) trend with ⟨ T e, ot ⟩ is connected to a strong inverse correlation between ⟨ T e, ot ⟩, n e, sep and ν *, thus directly linking changes in the divertor recycling moderated by ⟨ T e, ot ⟩ with the previously established relationship between ν *, core density peaking and core pressure resulting in a degradation in core plasma performance with decreasing ⟨ T e, ot ⟩ (increasing ν * ). A strong inverse correlation between the separatrix to pedestal density ratio, n e, sep / n e, ped, and ⟨ T e, ot ⟩ is also established, with the rise in n e, sep / n e, ped saturating at ⟨ T e, ot ⟩ > 10 eV. A strong reduction in H 98(y, 2) is observed as ⟨ T e, ot ⟩ is driven from 30 to 10 eV via additional D2 gas fueling, while the divertor remains attached. Consequently, the pronounced performance degradation in attached divertor conditions has implications for impurity seeding radiative divertor scenarios, in which H 98(y, 2) is already low (∼0.7) before impurities are injected into the plasma since moderate gas fueling rates are required to promote high divertor neutral pressure. A favorable pedestal pressure, p e, ped, dependence on I p has also been observed, with an overall increase in p e, ped at I p = 3.4 MA as ⟨ T e, ot ⟩ is driven down from attached to high-recycling divertor conditions. In contrast, p e, ped is reduced with decreasing ⟨ T e, ot ⟩ in the lower I p branches. Further work is needed to (i) clarify the potential role of edge opacity on the observed favorable pedestal pressure I p scaling; as well as to (ii) project the global and edge plasma performance trends with ⟨ T e, ot ⟩ to reactor-scale devices to improve predictive capability of the coupling between recycling and confined plasma fueling in what are foreseen to be more opaque edge plasma conditions.